What are the Spatial Linkage Patterns in East Kalimantan Region? - Lestari, Endah Kurnia; Muslihatinningsih, Fivien; As Shidqy, Achmad Faridh (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This research is original research that examines the spatial linkage between regions in East Kalimantan Province comprehensively Research Objectives: This study examines economic concentration and inter-regional connectivity and their impact on growth dynamics in East Kalimantan. Research Methods: This research uses a Spatial Autocorrelation Analysis based on Moran’s Index, Herfindahl-Hirschman Index, and Gravity Index. Data was analyzed from 10 regencies/cities in East Kalimantan from 2017 to 2023. Empirical Results: The study results indicate weak spatial integration among regencies/cities in East Kalimantan. Moran’s Index shows low positive spatial autocorrelation, suggesting limited economic spillover from high-GRDP regions. Market structure analysis reveals sectoral dominance, particularly in mining, leading to low diversification and oligopolistic tendencies. Gravity Index findings highlight strong spatial interaction between Kutai Kartanegara and Samarinda, while Mahakam Ulu remains isolated. Implications: This study shows that spatial linkages between regions in East Kalimantan remain weak, with the dominance of extractive sectors leading to a concentrated market structure and regional disparities. To address this, strategic regional planning is needed through improved connectivity, economic diversification, and the strengthening of non-extractive sectors. An inclusive and integrative policy approach is essential to achieve equitable and sustainable growth across the region. JEL Classification: O1, O18, R11, R12 How to cite: Lestari, E. K., Muslihatinningsih, F., & Shidqy, A. F. A (2025). What are the Spatial Linkage Patterns in East Kalimantan Region?. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 303-324. https://doi.org/10.15408/sjie.v14i2.45607.